2022
DOI: 10.3390/foods11081159
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antimicrobial Activity of Four Plant Essential Oils against Some Food and Phytopathogens Isolated from Processed Meat Products in Egypt

Abstract: Synthetic preservatives are widely utilized by the food industry to inhibit the microbial contamination and increase food safety and shelf life. The excessive utilization of synthetic preservatives can have a negative impact on human health and the environment. There is a great interest to find out natural substances as possible food-preservatives. The consumers’ preference for food products with natural ingredients prompted food manufacturers to utilize natural-based preservatives in their production. It is w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
(59 reference statements)
1
3
0
Order By: Relevance
“…Slight variations were observed but without any influence of the factors tested. This is in general agreement with the results of several studies conducted on different grape cultivars, such as Flame Seedless [23], which reported the MAP did not affect acidity, even with high %CO 2 (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) in the headspace [38]. On the other hand, the titratable acidity of Thompson Seedless decreased after 30 and 60 days of storage in air at 1 • C [40].…”
Section: Acidity Ph and Sscsupporting
confidence: 91%
See 1 more Smart Citation
“…Slight variations were observed but without any influence of the factors tested. This is in general agreement with the results of several studies conducted on different grape cultivars, such as Flame Seedless [23], which reported the MAP did not affect acidity, even with high %CO 2 (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) in the headspace [38]. On the other hand, the titratable acidity of Thompson Seedless decreased after 30 and 60 days of storage in air at 1 • C [40].…”
Section: Acidity Ph and Sscsupporting
confidence: 91%
“…For TBC analysis, 1 mL of previously prepared dilutions 10 −3 and 10 −5 were placed in a sterile Petri dish and about 15 mL of plate count agar media (Liofilchem, Roseto degli Abruzzi, Italy) was poured into the dish, and then incubated at 30 • C for 24 h [31]. Whereas, for TMC count one mL of previously prepared dilutions 10 −2 was placed in a sterile Petri dish and about 15 mL of PDA media was added, and then incubated at 22 ± 2 • C for 96-120 h under aerobic conditions [32]. The total bacteria (TBC) and mould (TMC) colonies in grapefruit samples were expressed as colony form units per millilitre (cfu/mL).…”
Section: Total Counting Bacteria and Mouldmentioning
confidence: 99%
“…Several EOs contain the very common cyclic monoterpene α-phellandrene, which exhibits a wide range of biological activity (Radice et al, 2022). The effectiveness and reduction of any pathogenic microorganism's resistance evolution are due to the synergism between the aromatic plant components (Elshafie et al, 2022). From our results, the investigated Gram-positive bacteria were found to be more sensitive to Eucalyptus essential oil than the tested Gram-negative.…”
Section: Discussionmentioning
confidence: 65%
“…Beyond their microbial-fighting attributes, these plant chemicals act as antioxidants, enhancing both color and flavor in plants. Applications of grape seed, oregano, clove, and cinnamon extracts have been reported to not only influence the color characteristics of food but also elevate its flavor profile (Baindara and Mandal, 2022;Coimbra et al, 2022;Elshafie et al, 2022;Khatri et al, 2023).…”
Section: Spices and Herbsmentioning
confidence: 99%
“…Despite advancements in research, the mechanisms of action of many natural antimicrobials remain incompletely understood (Elshafie et al, 2022). This lack of detailed understanding can hinder the precise control and optimization of these compounds for specific applications.…”
Section: Limited Understanding Of Mechanismsmentioning
confidence: 99%